THE ROLE OF THE PRINCIPAL AS A ROLE MODEL IN DEVELOPING EDUCATOR AND EDUCATIONAL STAFF HUMAN RESOURCES - Chasbullah , Wahib; Rindaningsih, Ida (Academic Journal Research, 2025)
Objective: This study investigates the strategic role of school principals in enhancing the competence and professionalism of educators and educational staff. It focuses on their role in managing infrastructure, providing continuous training, and optimizing technology to address evolving educational challenges. Methods: Using a literature review approach, this research identifies and examines key issues faced by school principals, including budget constraints, underutilization of technology, and the absence of systematic training programs. Results: The findings reveal that principals with transformational leadership styles significantly contribute to creating a positive, collaborative, and innovative work culture. Effective principals act as agents of change, improving the quality of learning and facilitating the integration of modern technological advancements into education systems. Novelty: This research underscores the pivotal role of school principals as transformational leaders and their potential to drive educational institutions toward a progressive future. It provides actionable recommendations for developing managerial and leadership strategies tailored to meet future educational demands.